Magnetically filtered vacuum-arc plasma deposition systems - Aksenov, I.I. (Вопросы атомной науки и техники, 2002)
This article is a brief historical review of R&D carried out by the KIPT scientists in the field of magnetic filtering of vacuum-arc plasma flows to be applied in thin film deposition technology.